Conversion of Wood Waste to be a Source of Alternative Liquid Fuel Using Low Temperature Pyrolysis Method - Gesyth Mutiara Hikhmah Al Ichsan; Khoirina Dwi Nugrahaningtiyas; Dian Maruto Widjonarko; Fitria Rahmawati; Witri Wahyu Lestari (Jurnal Kimia Sains dan Aplikasi, 2019)
Conversion of wood waste into bio-oil with low temperature pyrolysis method has been successfully carried out using tubular transport reactors. Pyrolysis carried out at temperatures of 250-300°C without using N2 gas. Bio-oil purified by a fractionation distillation method to remove water and light fraction compounds. The materials obtained from different types of wood waste, namely: Randu wood (Ceiba pentandra), Sengon wood (Paraserianthes falcataria), Coconut wood (Cocos nucifera), Bangkirei wood (Shorea laevis Ridl), Kruing wood (Dipterocarpus) and Meranti wood (Shorea leprosula). Bio-oil products are analyzed for their properties and characteristics, namely the nature of density, acidity, high heat value (HHV), and elements contained in bio-oil such as carbon, nitrogen and sulfur content based on SNI procedures, while bio-oil chemical compositions are investigated using Gas Chromatography Mass Spectroscopy (GC-MS). The maximum yield of bio-oil products occurs at 300°C by 40%. Bio-oil purification by fractional distillation method can produce purity of 16-31% wt. The characterization results of the chemical content of bio-oil showed that bio-oil of methyl formate, 2,6-dimetoxy phenol, 1,2,3 trimethoxy benzene, levoglucosan, 2,4-hexadienedioic acid and 1,2- benzenediol.